(untitled) (Research, Society and Development, 2022)
Infections during pregnancy are frequent and can cause severe complications, affecting the maternal-fetal binomial. Prenatal care is a classic example of prevention. A cross-sectional study was conducted with pregnant women to analyze the results of the nontreponemal test for syphilis and serologies for HIV 1/2, toxoplasmosis (IgM and IgG), hepatitis B and hepatitis C. The prevalences found were 4.9% (20/408), 0.24% (1/408), 20.83% (85/408), 0.49% (2/408), respectively for syphilis, HIV ½, toxoplasmosis (IgG) and HBV. No case of infection by the hepatitis C virus and acute toxoplasmosis (IgM) has been identified. It was possible to observe a high prevalence of syphilis, while the remaining infections had low prevalence. Screening for these infections is extremely important for the early diagnosis and treatment of pregnant women, avoiding maternal-fetal transmission and enabling better strategic planning for the prevention and early treatment of pregnant women.